Estratégia e competências : um estudo na indústria de fios da Cocamar Cooperativa Agroindustrial - Santin, Marcia (2006)
Until the 80's, the studies about strategies were focused in the external variable to the company. During the 80's and 90's, posture and cultural factors got space in the studies about strategy, valorizing the company's internal abilities and technologies. The competencies started then to be observed in the studies about strategies, but with different participations, now as a support to the strategies based upon the Michael Porter vision for example and other time as strategy participation based upon C. K. Prahalad and Gamel Hamel visions, where the competencies create a potential to differentiation. By this context, the main of this work was to make a study about the relationship between strategies and competencies in a spinning plant, counting on specific targets that aim to enthrall the concepts of strategies and competencies of the people that were interviewed, the vision of employees about the relationship between strategies and competencies and what is the relationship between strategies and competencies based on the review of literature. Concerning the review of literature, it was made an approach to several authors with different visions about strategies and competencies searching a support to the type of diagnosis verified in the field. Regarding the methodology, it was developed a study, with partily structured interviews and a documental analysis from thirteen employees, involving managers and supervisors and some operational workers. It was done an analysis of content of the data comparing to the review of literature, trying to get answers to the targets and specially, to the main target. The results we got led us to a secondary or sustainable alignment of competencies to strategy. By this result, it was suggested that there is a predominance of Michael Porter's strategies where the external aspects to the spinning plant were characterized and the competencies are secondly extended to help the management.